Pengaruh Carburizing Baja Karbon rendah Dengan variasi media Carburizer dan waktu penahan suhu Terhadap sifat fisis, Kekerasan dan keausan - Perpustakaan UGM, i-lib ([Yogyakarta] : Kantor Wakil Rektor Bidang Kemahasiswaan dan Alumni UGM, 2003)
," The research aims to investigate the influence of some carburizers with different holding temperatures of low carbon steel with 0.139 % C on microstructure, micro hardness and wear. The carburizers were charcoal, briquette, and coke, while the temperature was set to 900 ° C, 950° C, and 1000° C . A carburizing cylinder with a diameter of 50 mm and a height of 70 nun was used Natrium bicarbonate (Na2CO3) was used as energizer. The tested specimen was 20 mm long, 20 nun wide and 5 nun height. A heating furnace, a micro-hardness tester, a polisher, an optical microscope, and a wear tester were used for the experiment. The experiment was carried out in several steps. The first was crushing the carbon made of charcoal, briquette, and coke into powder and compressing the powder in a carburizer cylinder. In the second step, the specimen was put into the compressed powder and the cylinder was closed tightly. The third was putting the cylinder into the heating furnace until it reached the austenit (y) phase, and kept there for a while to allow homogeneity, and then cooled down slowly in the furnace. This process is called annealing. In the fourth step, the specimen was taken out of the cylinder and solidified by heating it up to reach the same phase and then dipped into water (quenching). The specimen was then tested and analyzed. The maximum hardness occurred to the charcoal carburizer treated in a temperature of 1000 C and was held in the temperature for two hours, with the value of 860 VHN in the outer part and 300 VHN the inner part. The minimum hardness happened to coke carburizer treated in a temperature of 900 C and was held in a temperature for two hours, with the value of 750 VHN in the outer part and 230 VHN the inner. The lowest wear rate was achieved by the carbonized charcoal processed in the temperature of 1000° C, with 0.0477 gr/mnt at 4000 rotations, and path as long as 129.5 cm. The microstructure photo was dominated by the hyper-eutectoid steel in the martensit phase and the hypo-eutectoid steel in the pearlite phase.